Mitochondrial Metabolism of Pyruvate Is Essential for Regulating Glucose-stimulated Insulin Secretion - Patterson, Jessica N. (American Society for Biochemistry and Molecular Biology, 2014)
It is well known that mitochondrial metabolism of pyruvate is critical for insulin secretion; however, we know little about how pyruvate is transported into mitochondria in β-cells. Part of the reason for this lack of knowledge is that the carrier gene was only discovered in 2012. In the current study, we assess the role of the recently identified carrier in the regulation of insulin secretion. Our studies show that β-cells express both mitochondrial pyruvate carriers (Mpc1 and Mpc2). Using both pharmacological inhibitors and siRNA-mediated knockdown of the MPCs we show that this carrier plays a key role in regulating insulin secretion in clonal 832/13 β-cells as well as rat and human islets. We also show that the MPC is an essential regulator of both the ATP-regulated potassium (K(ATP)) channel-dependent and -independent pathways of insulin secretion. Inhibition of the MPC blocks the glucose-stimulated increase in two key signaling molecules involved in regulating insulin secretion, the ATP/ADP ratio and NADPH/NADP(+) ratio. The MPC also plays a role in in vivo glucose homeostasis as inhibition of MPC by the pharmacological inhibitor α-cyano-β-(1-phenylindol-3-yl)-acrylate (UK5099) resulted in impaired glucose tolerance. These studies clearly show that the newly identified mitochondrial pyruvate carrier sits at an important branching point in nutrient metabolism and that it is an essential regulator of insulin secretion.